ESTIMATION OF THE SEASONAL VARIABILITY OF THE CONTENT OF HEAVY METAL COMPOUNDS IN THE RIVER WATERS OF THE FOOTHILL ZONE OF THE CENTRAL CAUCASUS - F.A. Atabieva; E.A. Cherednik (Водное хозяйство России: проблемы, технологии, управление)
Based on long-term data, the seasonal variability of the content of heavy metal compounds in the water of the rivers of the foothills of the Central Caucasus – the Terek, Malka, Baksan, Ardon, Cherek, and Urukh – was estimated. Generalizing studies affecting the regional characteristics of the level of hazardous heavy metals in the river waters of the foothill zone of the Central Caucasus have not been carried out over many years. Therefore, the objective of the study was to assess the level of hazardous compounds of heavy metals (Cr, Ni, Mo, Mn, Zn, Pb) in the water of the Terek, Malka, Baksan, Ardon, Cherek and Urukh rivers at 6 observation points located in the foothill zone of the Central Caucasus, for the period from 2005 to 2018. In the analysis, the atomic absorption method using the MGA-915M electrothermal atomizer was used. The level of heavy metal compounds in river water was evaluated by such characteristics as the long-term average and median concentrations, the range of concentration fluctuations, and the frequency of exceeding the maximum permissible concentration. An analysis of long-term data for the period 2005-2018 on the study of the level of heavy metal compounds in the water of the Baksan, Malka, Urukh, Terek, Cherek and Ardon rivers in the foothill zone of the Central Caucasus shows that river water pollution to a greater extent occurs in summer rain flood . The revealed levels of heavy metal compounds in river water over the long-term period under study, as well as the frequency of exceeding the maximum permissible concentration, are illustrated by graphs. The results obtained may be relevant in the development of regional water quality indicators.